MODELING OF WENNER CONFIGURATION RESISTIVITY USING 3D GALERKIN FINITE ELEMENT METHODS - Mawaddah, Saudiah
Resistivity method is one of the most commonly used geophysical exploration methods in providing subsurface structure information based on differences in resistivity. Calculation of resistivity values can be solved analytically or numerically. Analytical calculations are used to solve simple problems. Whereas for complex problems where solutions cannot be solved analytically a numerical solution will be used. One of the numerical methods used to solve resistivity calculations is to use the Finite Element Method. The finite element method is basically a method used to solve boundary conditions in differential equations. The basic concept of this method is based on the division of domains into smaller sub-domains and replacing all continuous domains with up to subdomains, where the node value of each element is represented by a simple interpolation function. In this final assignment, the writer conducts modeling using the Element Method to the Galerkin approach to obtain subsurface Pseudo-section resistivity for homogeneous and nonhomogeneous domains and to make 3D cube modeling to display the apparent resistivity values in the nonhomogeneous domain.